Segregação socioespacial e taxa de homicídios na área conurbada da Região Metropolitana de Maringá - Valotta, Fernanda Martins (2013)
Since the 1980's decade, the street violence is a phenomenon which has been configured such as a crucial issue to the Brazilian society. According to the World Health Organization - WHO, in the year 2000, one milion and six hundred thousand people lost their lives to some type of violence. Due to this scenario, reasearches aiming the analysis of the phenomenon of street violence can all be validated. This paper deals with such an important theme and it is aimed specifically towards the homicide rates because those dadas constitute the street violence indicators. This phenomenon is no longer kept within the bounds of large capitals, it is also, however, increasing all over the Brazilian hinterland regions. The districts of Maringá, Sarandi and Paiçandu in Paraná embodies the Metropolitan region which will be analysed due to its high homicide rates among other rates that are also part of the same metropolitan region. This reasearch will be composed by the identification of the relations presented within the social and spatial territory characterisctics where homicides take place, as well as the places where the victms of those crimes live. To establish a correlation between the homicide rate and the social organization of the territory will use the typology and socio Multivariate Linear Regression Model.